1991
DOI: 10.1007/bf01973722
|View full text |Cite
|
Sign up to set email alerts
|

Fate of carbaryl in rat skin

Abstract: Metabolism of carbaryl by rat liver and skin post-mitochondrial fraction has been measured in the presence and absence of cofactors to promote different metabolic pathways. The metabolic capacity was compared with the metabolism of carbaryl during percutaneous absorption in a static skin diffusion system using a variety of receptor fluids. Carbaryl was metabolised by hydrolysis, and ring hydroxylation followed by conjugation to the glucuronide or sulphate with liver post-mitochondrial fraction. Using skin post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Flow through diffusion cell systems have been developed to maintain the metabolic viability of skin in order to evaluate metabolism during percutaneous absorption (Macpherson et al 1991). Previous in vitro diffusion cell studies have demonstrated ADH activity during percutaneous absorption of retinyl palmitate in viable human and hairless guinea pig skin (Boehnlein et al 1994).…”
mentioning
confidence: 98%
“…Flow through diffusion cell systems have been developed to maintain the metabolic viability of skin in order to evaluate metabolism during percutaneous absorption (Macpherson et al 1991). Previous in vitro diffusion cell studies have demonstrated ADH activity during percutaneous absorption of retinyl palmitate in viable human and hairless guinea pig skin (Boehnlein et al 1994).…”
mentioning
confidence: 98%